(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper presents the result of generated electrical energy from mechanical energy using an electromagnetic generator. This generated energy is very low. Efforts are made to develop an energy storage device for this generated energy. Capacitor bank and rechargeable batteries are used for store energy. This stored energy is used to recharge the battery of wearable electronic devices for extending battery discharging time. Diode pump and voltage booster circuit are developed to enlarge output voltage. The voltage booster a circuit reaches to the maximum level of 5V at 1.2V input voltage. This generated voltage is stored in the capacitor bank and rechargeable battery.